2018
DOI: 10.2106/jbjs.16.01198
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Trends in Medical Complications Following 540,623 Primary Total Hip Replacements from a National Database

Abstract: Background:More than 75,000 total hip replacements were performed in England and Wales in 2014, and this figure is predicted to increase. Trends in mortality and complications following total hip replacement from 2005 to 2014 were evaluated to quantify risk and to identify “at-risk” groups to better inform recommendations for patient care.Methods:Our primary analysis estimated 90-day inpatient mortality following total hip replacement using Hospital Episode Statistics data from 2005 to 2014. Secondary analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 43 publications
1
38
1
Order By: Relevance
“…'major' versus 'minor' complications), reporting base (e.g. single-centre cohorts versus nationwide registries), and length of follow up [10][11][12][13][14] . For example, 90-day venous thromboembolism rates reported in a nationwide database analysis in South Korea were 3.9% for THA and 3.8% for TKA, whereas in-hospital symptomatic DVT rates as reported in a systematic review were 0.26% and 0.63% for THA and TKA respectively, and PE rates at 0.14% and 0.…”
Section: Introductionmentioning
confidence: 99%
“…'major' versus 'minor' complications), reporting base (e.g. single-centre cohorts versus nationwide registries), and length of follow up [10][11][12][13][14] . For example, 90-day venous thromboembolism rates reported in a nationwide database analysis in South Korea were 3.9% for THA and 3.8% for TKA, whereas in-hospital symptomatic DVT rates as reported in a systematic review were 0.26% and 0.63% for THA and TKA respectively, and PE rates at 0.14% and 0.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality in 90 days of Rudasill SE's study is 0.8%, while we have no patient died in three months after surgery. A ten-year national database from the UK also showed postoperative complications reduced year by year in THA, although the levels of comorbidity elevating [30]. Second, some THA-related complications such as dislocation, fracture, wound-healing delay, and vein thrombosis were not included by Rudasill SE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that overall rates of VTE after major orthopedic surgery are falling. A study from a national database from England and Wales of 10‐year trends (2005‐2014) in medical complications in 540 623 patients undergoing THA found that despite a population with increasing levels of comorbidity, the 90‐day mortality rate decreased from 0.60% to 0.15%, the 30‐day DVT rate decreased from 1.15% to 0.28%, and the 30‐day PE rate decreased from 0.77% to 0.40% . A recent systematic review of 255 studies that included almost 6.3 million patients found a consistent decline in mortality within 3 months after elective THA or TKA (from 1.15% pre‐1980 to 0.24% post‐2000) that was independent of method of prophylaxis .…”
Section: Epidemiology and Trends Over Time In Vte Occurrence After Mamentioning
confidence: 99%